Detection of Carrageenan in Cheese Using Lectin Histochemistry - Marie Bartlová; Matej Pospiech; Zdeňka Javůrková; Bohuslava Tremlová (Applied Sciences, 2021)
Carrageenan is a substance widely used as an additive in the food industry. Among other things, it is often added to processed cheese, where it has a positive effect on texture. Processing of such cheese involves grinding, melting and emulsifying the cheese. There is currently no official method by which carrageenan can be detected in foodstuffs, but there are several studies describing its negative health impact on consumers. Lectin histochemistry is a method that is used mainly in medical fields, but it has great potential to be used in food analysis as well. It has been demonstrated that lectin histochemistry can be used to detect carrageenan in processed cheese by Human Inspection and Computer-Assisted Analysis (CIE L*a*b*). The limit of detection (LoD) was established at 100 mg kg−1 for Human Inspection and 43.64 for CIE L*a*b*. The CIE L*a*b* results indicate that Computer-Assisted Analysis may be an appropriate alternative to Human Inspection. The most suitable parameter for Computer-Assisted Analysis was the b* parameter in the CIE L*a*b* color space.